Micro-solid phase extraction of polycyclic aromatic hydrocarbons in water using either C18 or molecularly imprinted polymer membranes: analytical merits and limitations - Mohd Sabari, Siti Nurul Umira; Loh, Saw Hong; Kamaruzaman, Sazlinda; Yahaya, Noorfatimah; Wan Mohd Khalik, Wan Mohd Afiq (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sample pre-treatment is often the bottleneck in an analytical process. Due to the drawbacks of conventional sample pre-treatment methods, microextraction utilizing lower amounts of adsorbents and organic solvents are therefore favoured. A micro-solid phase extraction (μ-SPE) technique coupled with gas chromatography-flame ionization detection (GC-FID) was successfully developed for the analysis of selected polycyclic aromatic hydrocarbons (PAHs), namely phenanthrene, fluoranthene, and pyrene, in environmental water. In this study, μ-SPE techniques using C18 and molecularly imprinted polymer (MIP) membranes were optimized, validated, and applied to the analysis of selected PAHs in environmental water samples. The analytical merits were compared, and the two methods were evaluated in terms of linearity, repeatability, and relative recovery. Under the optimal extraction conditions, both μ-SPE techniques using either C18 or MIP membranes as the adsorbents offered comparable ultratrace analysis of the selected PAHs in the range of 0.003 to 0.01 µg L–1. The extraction strength of C18 membranes was superior to that of MIP membranes for the extraction of low molecular weights PAHs from water in the presence of humic acid as a matrix factor. The C18 membranes overcome the non-covalence interaction between PAHs and humic acid and thus achieve better recovery.